Isolated superior mesenteric artery dissection: An unusual presentation quashed by an unusual approach - Waqas Ullah; Asif Mehmood; Mohsin Hamid; Maryam Mukhtar; Muhammad Atique Alam Khan (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Ullah W, Mehmood A, Hamid M, Mukhtar M, Khan MAA. Isolated superior mesenteric artery dissection: An unusual presentation quashed by an unusual approach. Turk J Gastroenterol 2019; 30(7): 648-51.